Offshore Platform Integration and Floatover Technology - Liu, Gengshen; Li, Huajun (Springer Tracts in Civil Engineering,, 2017)
This book discusses offshore platform integration technology, focusing on the floatover methodology and its applications. It also addresses topics related to safety and cost-effectiveness, as well as ensuring the success of a project through careful planning and established detailed operation procedure/working manuals, which are rarely found in the published literature. Unlike other publications in this area, the book not only includes details of technology development, but also presents real project cases in the discussion to make it more comprehensible. Each topic is illustrated with carefully created sketches to show the complex operation procedures. .